PENGARUH KEPEMIMPINAN VISIONER KEPALA SEKOLAH, BUDAYA ORGANISASI, DAN KECERDASAN EMOSIONAL GURU TERHADAP PENINGKATAN KINERJA GURU - Rumiati Masriah; Ruknan; Yulita Pujilestari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the influence of visionary leadership of school principals, organizational culture, and teachers’ emotional intelligence on the improvement of teacher performance in public elementary schools. The research employed a correlation study method, with data collected through questionnaires distributed to teachers in the Pondok Aren subdistrict. The results indicate that visionary leadership, organizational culture, and teachers’ emotional intelligence significantly affect teacher performance, both individually and simultaneously. Visionary leadership provides direction and motivation, organizational culture creates a positive and professional work environment, while emotional intelligence helps teachers manage emotions and enhance social interactions with students and colleagues. These findings highlight the importance of developing leadership, organizational culture, and emotional intelligence as strategies to improve educational quality.